3D Printing Artificial Blood Vessel Constructs Using PCL/Chitosan/Hydrogel Biocomposites. Issue 8 (27th February 2019) - Ulag, Songul; Kalkandelen, Cevriye; Oktar, Faik Nuzhet; Uzun, Muhammet; Sahin, Yesim Muge; Karademir, Betul; Arslan, Sema; Ozbolat, Ibrahim Tarik; Mahirogullari, Mahir; Gunduz, Oguzhan
Abstract: The present paper aims to overcome the problems related to previous use of autologous grafts using available synthetic grafts. To examine the optimum of the ideal vessel‐like constructs parameters are produced at 230 °C. At this production temperature, the elastic modulus values of the constructs ranges from 56 MPa to 174 MPa. The maximum cell proliferation is obtained from PCL/7wt.%CS/5wt.%H that is tested by mitochondrial dehydrogenase activity. The structures are visualized with all constructs after cell fixation by making use of the HUVEC cell line. Abstract : In this study, multi component system containing Alginate, Hyaluronic Acid, Collagen type I, PCL and Chitosan intended to be used by 3D printing. The combination of Alginate, Hyaluronic Acid and Collagen type I was called hydrogel and the effects of hydrogel concentration on chemical, thermal, mechanical, morphological and biocompatibility properties of the fabricated vessel constructs were investigated. This multicomponent system combined with 3D printing can be used for vascular tissue engineering applications.